Development of Pop-Up Book Media for Children’ Honest Characters - Sitti Hajrah; Irma Yuliantina; Sri Watini (Kirana Publisher (KNPub), 2026)
This study aims to produce a learning media in the form of a three-dimensional pop-up book used to instill honest character values ​​in early childhood and analyze the feasibility and effectiveness of its use in learning activities. This study uses a research and development method with a four-stage model that includes the stages of definition, design, development, and dissemination. The research subjects were 30 children aged 5-6 years from three kindergartens in Pijoan Village, Muaro Jambi Regency. Research data were collected through observation, interviews, expert validation, and implementation of initial and final tests. Product feasibility was analyzed through assessments by material experts, media experts, and language experts, while the effectiveness of the media was analyzed based on the improvement in the development of children's honest character. The results of the study showed that the developed three-dimensional pop-up book media obtained a very feasible category based on the results of expert validation. In addition, the results of the field trial showed an increase in the development of children's honest character, as seen from the increase in the average score from 43.5% in the initial test to 68% in the final test with a moderate level of improvement. Thus, three-dimensional pop-up books can be used as an interesting and effective learning media in instilling honesty values ​​in early childhood.